SUPERVISI AKADEMIK KEPALA SEKOLAH DALAM MENINGKATKAN MUTU GURU - Manner Tampubolon (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2019)
One effort to improve teacher professional quality is through academic supervision. The implementation of academic supervision needs to be carried out systematically by the principal, aiming to provide guidance to teachers so that they can carry out their duties effectively and efficiently. The implementation of supervision is not to find fault with the teacher but the implementation of supervision is basically the process of providing assistance services to teachers to improve the teaching and learning process conducted by teachers in improving the quality of learning outcomes. Planned, systematic and directed academic supervision is expected to improve teacher quality. The realization of these goals is not an easy thing. This is because the actualization of the teacher's ability depends on various components of the education system that collaborate with each other. And of course the role of the principal as a supervisor in the school where his assignment must be maximized. Keywords: Academic supervision, Principal, Teacher Quality.